Credit Constraints and the North-South Transmission of Crises - Nguyen, Ha (2012)
Adverse shocks to rich countries often have a large and persistent negative impact on investment and output in developing countries. This paper examines a transmission mechanism that can account for this stylized fact. The mechanism is based on the existence of international financial frictions. Specifically, if a small, developing country has to collateralize its assets to borrow funds to invest, falling asset prices caused by a negative shock in an advanced economy worsen the developing country's collateral value and reduce its ability to borrow and reinvest. Hence, investment in the developing country declines, and international investors repatriate capital to the advanced country. As less capital now can be pledged as collateral, the developing country's credit constraint is further tightened, which leads to another round of decline in investment. This generates a downward spiral that may cause large output losses to the developing country. The mechanism finds empirical support in the 2008-2009 crisis data.